Association of Health-Related Quality of Life with Functional and Radiological Outcomes in Patients with Rheumatoid Arthritis–Associated Interstitial Lung Disease, Systemic Sclerosis–Associated Interstitial Lung Disease, and Idiopathic Pulmonary Fibrosis - Sahinoğlu, Irem; Kizilirmak, Deniz; Uslu, Sadettin; Kacar, Mevlüt; Tasgöz, Filiz Cemre; Sülükcü, Seref; Acar, Emre Ali; Gencer Tuluy, Müge; Sari, Secil; Soysal Gündüz, Ozgül; Pirildar, Timur (Archives of Rheumatology, 2025)
Background/Aims: This study aimed to investigate the association between lung function and imaging parameters with health-related quality of life (HRQoL), as measured by the St. George’s Respiratory Questionnaire (SGRQ), in patients with rheumatoid arthritis–associated interstitial lung disease (RA-ILD), systemic sclerosis–associated ILD (SSc-ILD), and idiopathic pulmonary fibrosis (IPF). Materials and Methods: In this cross-sectional study, a total of 120 patients (37 RA-ILD, 42 SSc-ILD, and 41 IPF) were included. Demographic, clinical, functional (forced vital capacity [FVC], lung diffusion capacity for carbon monoxide [DLCO], 6 minute walk test), and radiological (Warrick scores) data were collected. The associations between SGRQ scores and these parameters, as well as other patient-reported outcome measures (PROMs), were analyzed. Results: St. George’s Respiratory Questionnaire scores showed significant correlations with functional measures and PROMs across all groups. However, no correlation was found between SGRQ and FVC only in RA-ILD. In SSc-ILD and IPF, SGRQ scores were also significantly associated with high-resolution computed tomography–based Warrick scores. However, no correlation was found between SGRQ and radiological parameters in RA-ILD. Receiver operating characteristic (ROC) analysis demonstrated that SGRQ could help identify patients with impaired lung function (FVC <70%) in IPF and SSc-ILD groups. Conclusion: St. George’s Respiratory Questionnaire may be a valuable tool for evaluating HRQoL in patients with SSc-ILD and IPF, with moderate associations with functional and radiological outcomes. Its utility in RA-ILD appears to be more limited and requires further investigation.